The Relationship between Partner Support and Interdialytic Weight Gain (IDWG) Hemodialysis Patient - Mundakir Mundakir; Nur Fadlilah; Retno Sumara; Asri Asri; Yuanita Wulandari (Jurnal Ners, 2019)
Introduction: Patients undergoing hemodialysis experience an influence in terms of the biological, psychological, social and spiritual problems that they encounter. In particular, there are biological aspects that affect weight gain between dialysis sessions. In terms of the psychological aspect, there is an influence on emotional vulnerability, such as anxiety, fear and despair. They need family support, especially as part of a couple. This study aimed to determine the relationship between partner support and IDWG in hemodialysis patients.Methods: This study used a descriptive cross-sectional design. The population consisted of 60 hemodialyzed people. The sample was recruited using purposive sampling, resulting in 42 respondents who met the inclusion criteria. The study was conducted in a Private Hospital in Surabaya. The independent variable was partner support and the dependent variable was the IDWG in the hemodialysis patient. The data was collected through a questionnaire and it was analyzed using the Spearman test.Results: The results show that there was a relationship between partner support and IDWG hemodialysis patients with p = 0.025 (α ≤0.05).Conclusion: Good partner support reduces the low IDWG in hemodialysis patients. Therefore, determining the level of family support especially that given by a partner of a IDWG hemodialysis patients will positively support better IDWG hemodialysis patients, thus preventing them from the potential side effects of IDWG such as hypotension, muscle cramps, shortness of breath and cardiovascular problems.